TRAUMATIC AND ANEURYSMAL JAW CYSTS: DIFFICULTIES OF THE DIAGNOSIS - P.I. Tkachenko; I.I. Starchenko; S.O. Bilokon; N.V. Lokhmatova; N.P. Bilokon; Y.V. Popelo (Український стоматологічний альманах)
The great diversity of the jaw cysts makes the issues of their diagnosis, differential diagnosis, and treatment quite important, always requiring an individual approach, given the features of each clinical case.